TAMI-10. CHARACTERIZATION OF CANCER-ASSOCIATED FIBROBLASTS IN GBM AND DEFINING THEIR PRO-TUMORAL EFFECTS. (12th November 2021) - Jain, Saket; Rick, Jonathan; Joshi, Rushikesh; Beniwal, Angad; Spatz, Jordan; Chang, Alexander; Nguyen, Alan; Shudir, Sweta; Chandra, Ankush; Haddad, Alexander; Wadhwa, Harsh; Shah, Sumedh; et al.
Abstract: Cancer-associated fibroblasts (CAFs) constitute a key component of the tumor microenvironment. While pro-tumoral CAFs have been identified in some cancers, CAFs had been presumed absent in glioblastoma given the lack of brain fibroblasts. We found that serial trypsinization of primary glioblastoma cultures yields cells that morphologically resemble fibroblasts and transcriptomically resemble CAFs as shown by bulk RNA-seq and single-cell RNA-seq. Moreover, Single-cell RNA-seq from patient GBMs showed a mesenchymal lineage for CAFs. We demonstrate that Glioblastoma CAFs are chemotactically attracted to glioblastoma stem cells (GSCs) and CAFs enriched GSCs. To identify CAF/GSC interaction mediators, we created a resource of inferred crosstalk by mapping the expression of receptors to their cognate ligands/agonists. This analysis suggested PDGF-b and TGF-b as mediators of GSC recruitment and proliferation of CAFs, and osteopontin and hepatocyte growth factor (HGF) as mediators of CAF-induced GSC enrichment, hypothesis confirmed by blocking antibodies. Glioblastoma CAFs also induce hypertrophied vessels and M2 macrophage polarization, the latter through unique CAF production of the EDA fibronectin variant which binds macrophage toll-like receptor 4 (TLR4) in a targetable manner. Glioblastoma CAFs were enriched in the subventricular zone which houses the neural stem cells that produce GSCs. Depleting CAFs in GSC-derived xenografts slowed their in vivo growth. These findings are among the first to identify glioblastoma CAFs and reveal their involvement with GSCs, making them an intriguing target.